Enhancing Students’ Academic Achievement in Biology using Projected Instructional Media - Adebanjo, Adedoyin A.; Shogunle, Olujoke Omodoyin (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This study investigated how projected instructional media could enhanced students’ academic achievement in biology. It also determined whether the performance of the students would vary with gender when exposed to projected instructional media. It employed pre-test, post-test, control group quasi-experimental design. The sample consisted of sixty five students offering biology. Two schools were purposively selected in Ijebu East Local Government Area based on certain criteria. Two schools were randomly selected to form experimental and control groups. Two null hypotheses were formulated and tested at 0.05 level of significance. Two instruments were used for the study. Analysis of Covariance and t-test were used for data analysis. Findings indicated that students taught biology using projected instructional media performed better than those taught using conventional method of teaching. In addition, there was no significant difference between the mean scores of male and female students taught biology using projected instructional media. Based on the findings, it was recommended among other that secondary school biology teachers should effectively make use of projected instructional media in teaching the students the abstract and difficult concepts in biology irrespective of gender. Keywords: Projected Instructional Media, Biology, Students’ Academic Achievement, Gender.